Mn(II) Removal From Ground Water by Using Ipomea batatas Carbon - Emmanuel, K.A.; Veerabhadra Rao, A.; Ramesh Raju, K. (Asian Journal of Chemistry, 2010)
The aim of this study is to investigate the preparation of low-cost activated carbon from Ipomoea batatas (IBC) and to explore their potential application for the removal of heavy metals from aqueous solutions. Conventional physical (water vapour) activation was used for synthesizing the adsorbent. The obtained carbon was employed for the removal of Mn(II) from aqueous solutions at different initial concentrations and pH values. Adsorption of Mn(II) ion follows Langmuir isotherm, the maximum loading capacity for Mn(II) ion is 23.4 mg g-1. According to the experimental data it can be inferred that the basic character of the surface, i.e., the high content of basic groups, favours adsorption of ion. Regarding manganese adsorption herein obtained carbon presented higher uptake adsorption than that of activated carbons reported in the literature.